Pharmaceutical Pricing and Reimbursement Policies in Switzerland - Paris, Valérie (OECD Health Working Papers, 2007)
This paper examines aspects of the policy environment and market characteristics of the Swiss pharmaceutical sector, and assesses the degree to which Switzerland has achieved certain policy goals. In Switzerland, pharmaceutical spending has not been growing faster than health expenditure as a whole, as has been the case in many other OECD countries. Swiss pharmaceutical spending per capita and as a share of GDP is modest by OECD standards. This in part reflects relatively low levels of pharmaceutical consumption, given that public prices are among the highest in Europe and the Swiss tend to be early adopters of new pharmaceutical products. Switzerland's regulation of prices for reimbursed drugs, based on referencing across countries and within the therapeutic class for products with comparators, appears to result in prices lower than what would be obtained absent regulation. Although ex-manufacturer prices are somewhat high relative to other European countries, recent reforms have reduced the differential. While costs are under control, Switzerland has scope to improve the cost-effectiveness of its expenditures in the pharmaceutical area. Generic penetration of the market is increasing but falls short of what has been achieved elsewhere and the prices of generic products are higher than what is found in other countries. Relatively high mark-ups over ex-factory prices suggest that the distribution chain is a source of further potential efficiencies, although high costs could also reflect characteristics of the Swiss economy...